2019
DOI: 10.1111/acer.13965
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Use of Alcohol Treatment Services and Reasons for Nonuse in a National Sample

Abstract: Background: The majority of adults with alcohol use disorders do not obtain help, and women are less likely to utilize alcohol services than men. We sought to quantify gender differences in alcohol services utilization, overall and by type, using national longitudinal data and to explore potential gender differences in perceived need for help and reasons for not seeking help.Methods: We analyzed data from the National Epidemiologic Survey on Alcohol and Related Conditions from White, African American, and Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 57 publications
2
63
0
2
Order By: Relevance
“…It should be noted that there was a high correlation between help‐seeking and treatment utilization in this study, but we chose to report and discuss them separately due to their conceptual and clinical distinctions. There were many notable differences in overall service use across generation, some of which interacted with sex and revealed new insights into the known fact that females seek use fewer services than males (Alvanzo et al, ; Chartier and Caetano, ; Gilbert et al, ; Ilgen et al, ; Raimo et al, ). Regardless of generation, younger females were less likely than males to seek help or utilize treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that there was a high correlation between help‐seeking and treatment utilization in this study, but we chose to report and discuss them separately due to their conceptual and clinical distinctions. There were many notable differences in overall service use across generation, some of which interacted with sex and revealed new insights into the known fact that females seek use fewer services than males (Alvanzo et al, ; Chartier and Caetano, ; Gilbert et al, ; Ilgen et al, ; Raimo et al, ). Regardless of generation, younger females were less likely than males to seek help or utilize treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the generational differences in service use found in the current study interacted with sex, and there were also significant sex differences by themselves. It has been repeatedly found that females are less likely than males to utilize services for AUD (Alvanzo et al, ; Chartier and Caetano, ; Gilbert et al, ; Raimo et al, ). The current findings align with this and add additional insights.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations